ANALYSIS OF FRACTIONAL ANISOTROPY (FA) VALUES AND APPARENT DIFFUSION COEFFICIENT (ADC) VALUES IN ISCHEMIC STROKE DISEASES OF MRI GE 3 TESLA - Mustofa, Ali; Sensusiati, Anggraini Dwi; Muhaimin, Muhaimin; Utomo, Sri Andreani; Latifah, Risalatul (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: Diffusion Weighted Imaging and Diffusion Tensor Imaging is an advanced technique in MRI that shows the diffusion in brain of ischemic stroke disease. Diffusion Weighted Imaging (DWI) shows the lesions without gadolinium contrast agent and produce Apparent Diffusion Coefficient values. Whereas, Diffusion Tensor Imaging (DTI) shows connectivity's of central nervous system that cannot be seen by using conventional MRI. Diffusion Tensor Imaging produces Fractional Anisotropy values. Purpose:This study has aim to analyze the Apparent Diffusion Coefficient values and Fractional Anisotropy values in Stroke Ischemic disease. Method: Total samples used are 14 samples, consist of 7 (50%) man and 7 (50%) woman with ischemic stroke disease. Each sample deals by Diffusion Weighted Imaging and Diffusion Tensor Imaging sequences. The Region of Interest (ROI) is placed in ischemic stroke lesions and contra lateral side of lesions. Result: The result shows that 9 samples of brain tissue lesions located in the right side and 5 samples in the left side. Right lesions have the average ADC stroke: 0.001748; normal ADC: 0.000954; FA stroke: 0.144522; and normal FA: 0.426111. While, left lesions have the average ADC strokes 0.000979; normal ADC: 0.000835; FA stroke: 0.2556; and normal FA 0.4324. Conclusion: So, the conclusion of this study is Apparent Diffusion Coefficient (ADC) values in case of ischemic stroke can decreases or increases depend on the age of stroke. While, the Fractional Anisotropy (FA) values will decrease without being affected by age of stroke.